User-Centered Design Pada User Interface (UI)/ User Experience (UX) Aplikasi Lab Me - Muhammad Miftahul Haq; Dani Firmanto; Fredy Susanto; Triono Triono (Universitas Islam Raden Rahmat, Malang, 2024)
The Lab Me application is an item data collection application for computer laboratories. As time goes by, manual data collection has become far behind and is ineffective, errors often occur when collecting data on goods which give rise to new problems, so we need an application that will make it easier to collect data on goods. by applying the User-Centered Design (UCD) method. The UCD approach is used to ensure that user needs and preferences are the main focus in the application design and development process. To collect data regarding user needs and preferences, questionnaires were distributed to IT staff who manage computer laboratories. The research results show that the application of the UCD method in developing the Lab Me application has succeeded in increasing user satisfaction and efficiency in the computer laboratory equipment inventory management process. From the test results using the black box method with 10 respondents, 90% said they were satisfied and 10% said they were dissatisfied. This application is expected to be an effective solution in supporting laboratory operational activities, especially in terms of data collection and equipment tracking.